Red blood cell volume and the capacity for exercise at moderate to high altitude - Jacobs, R. A.; Lundby, C.; Robach, P.; Gassmann, M. (Sports Medicine, 2012)
Hypoxia-stimulated erythropoiesis, such as that observed when red blood cell volume (RCV) increases in response to high-altitude exposure, is well understood while the physiological importance is not. Maximal exercise tests are often performed in hypoxic conditions following some form of RCV manipulation in an attempt to elucidate oxygen transport limitations at moderate to high altitudes. Such attempts, however, have not made clear the extent to which RCV is of benefit to exercise at such elevations. Changes in RCV at sea level clearly have a direct influence on maximal exercise capacity. Nonetheless, at elevations above 3000?m, the evidence is not that clear. Certain studies demonstrate either a direct benefit or decrement to exercise capacity in response to an increase or decrease, respectively, in RCV whereas other studies report negligible effects of RCV manipulation on exercise capacity. Adding to the uncertainty regarding the importance of RCV at high altitude is the observation that Andean and Tibetan high-altitude natives exhibit similar exercise capacities at high altitude (3900?m) even though Andean natives often present with a higher percent haematocrit (Hct) when compared with both lowland natives and Tibetans. The current review summarizes past literature that has examined the effect of RCV changes on maximal exercise capacity at moderate to high altitudes, and discusses the explanation elucidating these seemingly paradoxical observations.